Vitiligo Review: etiopathogenesis, diagnosis and treatment - Aleksandra Witek; Jakub Parys; Agnieszka Mikosińska; Martyna Kaźmierczak; Maciej Mossakowski; Patrycja Kałuziak; Marta Jajczak; Mateusz Litwin; Stanisław Jesionek; RAfał Bieś (Quality in Sport)
Introduction and purpose:This review is intended for healthcare professionals, including dermatologists, primary care physicians, and researchers, who seek a comprehensive understanding of vitiligo. It is also relevant for patients and their families to better understand the condition. The review is indicated for those dealing with cases of vitiligo that are difficult to diagnose or manage, those with widespread or refractory vitiligo, and individuals interested in the latest advancements in treatment. The purpose of this review is to provide a detailed analysis of vitiligo’s etiopathogenesis, the current diagnostic methods, and the most effective treatment options. By exploring the genetic, autoimmune, and environmental factors involved in vitiligo, the review aims to enhance the understanding of the disease's origin and progression. Additionally, it seeks to offer evidence-based insights into the most up-to-date diagnostic tools and therapeutic approaches, ultimately improving patient care and guiding future research directions.